A comparative absorption study of sucrosomial® orodispersible vitamin D3 supplementation vs. a reference chewable tablet and soft gel capsule vitamin D3 in improving circulatory 25(OH)D levels in healthy adults with vitamin D deficiency—Results from a prospective randomized clinical trial - Bano, Aasiya; Abrar, Saida; Brilli, Elisa; Tarantino, Germano; Bugti, Ali Akbar; Fabbrini, Marco; Conti, Gabriele; Turroni, Silvia; Bugti, Mahroo; Afridi, Fauzia; Mureed, Shah; Zada, Hakeem; et al. (Frontiers in Nutrition, 2023)
Background Vitamin D (Vit D) deficiency (VDD), associated with diverse health conditions, is commonly treated with Vit D3 supplements. However, the gastrointestinal (GI) absorption of Vit D3 in different formulations has not been well studied. Objective We aimed to compare the absorption of an innovative phospholipids-sucrester matrix biodelivery vehicle-based (sucrosomial®) orodispersible Vit D3 preparation against a reference chewable tablet and soft gel capsule (SGC) Vit D3 formulations in Vit D-deficient healthy adults. Methods In study 1, 25 subjects were randomized to receive a weekly single dose of 200,000 IU of sucrosomial® Vit D3 (n = 12) or chewable tablet Vit D3 (n = 13) for 3 weeks. In study 2, 20 subjects were randomized to receive a single dose of 200,000 IU every other week of sucrosomial® Vit D3 (n = 10) or SGC Vit D3 (n = 10) for 6 weeks. Circulatory 25-hydroxyvitamin D3 [25(OH)D] levels were reassessed after 2, 3, and 6 weeks in study 1 and after 4 and 6 weeks in study 2. Results In study 1, after 2 weeks, circulatory 25(OH)D levels increased significantly in both Vit D3 treatment groups (p < 0.0001) but improved markedly in the sucrosomial® Vit D3 group, with no further considerable change after 3 and 6 weeks in both groups. Overall, at all three follow-ups, sucrosomial® Vit D3 treatment achieved significantly higher and sustained 25(OH)D levels (p < 0.001). In study 2, after 4 weeks, both Vit D3 treatment groups showed significant improvement in circulatory 25(OH)D levels (p < 0.0001) but substantially higher in the sucrosomial® group with statistically significant differences between the two treatment groups (p = 0.02). At the 6-week follow-up, only subjects in the sucrosomial® Vit D3 group showed a further increase in circulatory 25(OH)D levels (p = 0.049), but no further significant changes in the levels of the SGC Vit D3 group (p = 0.062), showing a statistically significant difference between the two treatment groups (p = 0.002). The Vit D3 treatment was well tolerated by all participants, and no treatment-emergent effects or serious adverse events were reported. Conclusion Our results suggest that the sucrosomial® Vit D3 preparation absorbs efficiently in the GI system, achieving adequately higher and sustained circulatory Vit D levels in VDD, and thus can effectively contribute to the body protection against VDD-associated health conditions. Clinical trial registration clinicaltrials.gov, identifier: NCT05706259.